2019
DOI: 10.36671/mumtaz.v2i2.29
|View full text |Cite
|
Sign up to set email alerts
|

Membumikan Dakwah Berbasis Komunikasi Profetik Di Era Media Baru

Abstract: As a means of disseminating information, a new era of media does not always have a positive impact on the purpose of da’wah. The new era’s media actually raises the birth of da’wah that is extreme, radical and far from the meaning of Islam as a religion of peace. Very few da’wah actors and activists have integrated prophetic ethics and values in the new media era. They use many utterances of hatred (hatespeech) and lies (hoaxes) to preach. This phenomenon is very inversely proportional to the teachings of frie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a concept and strategy for da'wah 'Ayun (2018) research was also confirmed through Muh. Aswad, et al about "Konsep Komunikasi Profetik (kenabian) Sebagian Strategi Dakwah" (2022).…”
Section: Introductionmentioning
confidence: 78%
“…As a concept and strategy for da'wah 'Ayun (2018) research was also confirmed through Muh. Aswad, et al about "Konsep Komunikasi Profetik (kenabian) Sebagian Strategi Dakwah" (2022).…”
Section: Introductionmentioning
confidence: 78%